Dossier II: Estudio pericial de firmas automodificadas fraudulentamente e inventadas - Piñeyro Cuevas, Alberto (Quadernos de criminología, 2020)
Fraudulently self-modified and invented signatures are studied by Handwriting. The foundations, methods and techniques of this discipline allow comparing this type of signature with undisputed samples, in order to identify the coincidences and/or differences which confirm or discard the authorship of the doubtful signature. This article presents an experiment consisting of the expert analysis of the fraudulently self-modified and invented signatures.